2009
DOI: 10.3928/15394492-20090825-01
|View full text |Cite
|
Sign up to set email alerts
|

Hands-On Learning versus Learning by Demonstration at Three Recall Points in University Students

Abstract: This randomized study compared the effect of two teaching/learning methods (hands-on versus demonstration) on immediate, 15-minute, and 24/48-hour recall in 60 university students. Each student either made no-bake cookies or observed the demonstrated process. Inter-rater reliability concerning recall scores was strong (intraclass correlation coefficient = .98). Analysis of variance across all three levels of recall supported the hands-on condition (F [1,58] = 4.45, p = .039). However, only one of the three t t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 5 publications
1
11
0
2
Order By: Relevance
“…Experiential learning is learning that is derived from one's experiences; it has been cited as one of the most effective learning activities (Hearns, Miller, & Nelson, 2009; Poudel et al., 2010; Randler & Hulde, 2007), and outside of actually working on real‐life problems (i.e., field work), it has been successful in soil science based on student surveys (Field et al., 2011). Kolb (1984) developed a holistic model of the experiential learning process.…”
Section: Introductionmentioning
confidence: 99%
“…Experiential learning is learning that is derived from one's experiences; it has been cited as one of the most effective learning activities (Hearns, Miller, & Nelson, 2009; Poudel et al., 2010; Randler & Hulde, 2007), and outside of actually working on real‐life problems (i.e., field work), it has been successful in soil science based on student surveys (Field et al., 2011). Kolb (1984) developed a holistic model of the experiential learning process.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many educational studies performed on the analysis and comparison of these methods. In particular, several results (Hearns, Miller, & Nelson, 2010;Kontra, Lyons, Fischer, …”
Section: Introductionmentioning
confidence: 99%
“…11,12 Comparison of this type of learning to demonstration learning concluded that hands-on learning had higher recall scores. 13 Proper nutrition is essential for cancer prevention, and is important during and after treatment. With limited resources at community cancer centers, more research is needed to determine the best strategies for effective cancer interventions and nutrition education.…”
Section: Introductionmentioning
confidence: 99%